The relationship between decision-making time and accuracy of jump shooting among students at the college of physical education and Sports Sciences in handball - Obaid, Mustafa Ahmed (Journal of Physical Education, 2026)
The study aimed to analyze the nature of the relationship between decision-making time and the accuracy of shooting by jumping among handball players who are students of the fourth stage at the College of Physical Education and Sport Sciences to reveal the extent to which cognitive-motor ability contributes to improving offensive skill performance. The study adopted a descriptive approach using the method of relational relationships, and 20 players who were selected deliberately participated. The study used a reaction time system to measure decision time, as well as test the accuracy of shooting from jumping from three specific points within the attack area. The results showed that the Arithmetic mean decision time was 0.828 seconds, while the Arithmetic mean successful shooting attempts from the jump shooting were 69.24out of 10. Statistical processing also revealed a statistically significant negative correlation between the two variables of r = -0.84, indicating that the lower the decision time, the higher the shooting accuracy from jumping. These results indicate that the higher the player’s possessed speed in analyzing the situation and making decisions, this was directly reflected in a more accurate ability to direct the ball while jumping, which is consistent with the principles of sensorimotor perception and the theory of information processing in sports performance. The study recommends the need to integrate special training to reduce decision-making time into training programs for attackers, such as changing attitudes, visual and auditory response exercises, as well as the use of electronic measuring devices to enhance skill development. He also recommends future studies that address other psychomotor variables such as selective attention and motor prediction speed to develop the performance of offensive positions in handball.